Teachers Perception on Tobacco Free School in Bangladesh - Rahman, Md Mizanur; Ahmad, Skeikh Akhtar; Karim, Jahirul; Pangkas, Johnny; Hun, Teh Jo; Suhaili, Mohd Raili bin (Bangladesh Journal of Medical Science, 2015)
Introduction: Comprehensive tobacco-free school policy benefits everyone by reducing exposure to second-hand smoking and creating a system that reinforces tobacco-free norm and attitudes, which in turn affect tobacco use having an impact on the health of the community. Objective: This study aims to assess the perception of teachers on tobacco free school environments and factors supporting it. Methods: A two-stage cluster sampling technique was used for the selection of schools with selection probability proportional to enrolment size followed by stratified random sampling of government and private schools. Data were collected from 559 secondary school teachers using a structured questionnaire. Results: Estimation indicated that 48.3% (95% CI: 44.5%, 52.6%) of the teachers were less supportive and 51.7% (95% CI: 47.4%, 55.5%) were more supportive for smoking free school. Logistic regression analysis revealed that non tobacco user teachers were more likely to be supportive (OR=1. 891, 95% CI: 1.197, 2.986) for tobacco free school. However, no statistically significant association was found between perceived supportive tobacco free school and age, sex, level of education, type of school and family size (p>0.05). Exposure to second hand smoking and curriculum content of tobacco issues were not significantly related with tobacco free school. Conclusion: Comprehensive school based programme with participation of school personnel and community can effectively implement tobacco free school programmes. Bangladesh Journal of Medical Science Vol.14(3) 2015 p.274-279